Determination Of Financial Performance Ratio In Prediction Of Financial Distress In Cigarette Companies Listed On The Indonesia Stock Exchange - Fatmawati, Elsye; Oktavyani, Dini (Proceeding International Pelita Bangsa, 2023)
This study aims to partially examine the effect of liquidity ratios, leverage, profitability and sales growth ratios on financial distress. The population in this study were all cigarette companies listed on the Indonesia Stock Exchange and the sample was taken using saturated sampling method to obtain 30 samples from 5 companies. The data processing technique uses multiple linear analysis with the help of the statistical program Eviews version 12 as a tool. The results of this study indicate that the variable liquidity has a positive and significant effect on financial distress. Leverage has negative results and has no significant effect on financial distress. Profitability has a positive and significant effect on financial distress. Sales growth gives positive results but does not have a significant effect on financial distress.